2009
DOI: 10.1177/0890334409333422
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Cancer Patients' Experiences Using Donated Human Milk

Abstract: This represents the first published account from the patient's perspective of the use of human milk as cancer therapy. Purposive sampling was used to select a sample of 10 participants. Five were patients and 5 were family proxies. Individual interviews were conducted using confirmatory interviewing technique to obtain individual perspectives on the motivation for cancer patients to take donated human milk. Human milk therapy improved the quality of life (QOL) measures in the physical, psychological, and spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
9
0
1
Order By: Relevance
“…Furthermore, there are several case reports where donor milk was used in adults with special medical conditions, e.g. in liver transplanted patients who were IgA deficient to supply extra IgA [25] or in adult cancer patients [26] .…”
Section: Who Are the Recipients Of Donor Milk?mentioning
confidence: 99%
“…Furthermore, there are several case reports where donor milk was used in adults with special medical conditions, e.g. in liver transplanted patients who were IgA deficient to supply extra IgA [25] or in adult cancer patients [26] .…”
Section: Who Are the Recipients Of Donor Milk?mentioning
confidence: 99%
“…A qualitative retrospective study of 20 cancer patients who drank human milk as a complementary or alternative therapy reported that patients or their proxies found that human milk consumption did not change their disease outcome (215). The patients appear to have received a psychological benefit from the possibility of hope from this unproven therapy (215).…”
Section: Are Hamlet-like Compounds Formed In Nature?mentioning
confidence: 99%
“…The patients appear to have received a psychological benefit from the possibility of hope from this unproven therapy (215). Some patients drank raw human milk.…”
Section: Are Hamlet-like Compounds Formed In Nature?mentioning
confidence: 99%
“…Недавно опубликованы сведения, что терапия донорским грудным молоком улучшает психологическое и духовное восприя-тие качества жизни у группы пациентов с раком различ-ных форм, органов и систем [26].…”
Section: при невозможности обеспечения ребенка материнским молоком неunclassified